Low Gestational Weight Gain in Obese Women and Pregnancy Outcomes - Moehlecke, Milene; Costenaro, Fabíola; Reichelt, Angela AJ; Oppermann, Maria Lúcia R.; Leitão, Cristiane B. (American Journal of Perinatology Reports, 2016)
Obesity during pregnancy and excessive weight gain during this period are associated with several maternal–fetal and neonatal complications. Moreover, a significant percentage of women have weight retention in the postpartum period, especially those with excessive weight gain during pregnancy. The recommendations of the 2009 Institute of Medicine were based on observational studies that have consistently shown that women with weight gain within the recommended range had better outcomes during pregnancy. In patients with obesity, however, there is no recommendation for weight gain, according to the class of obesity. This review, therefore, aims to evaluate the evidence on key maternal and fetal complications related to low weight gain during pregnancy in obese and overweight patients.
Keywords: gestational weight gain; pre-pregnancy body mass index; pregnancy outcomes; obesity